Noncontact Atomic Force Microscopy Volume 2 - Morita, Seizo.; Giessibl, Franz J.; Wiesendanger, Roland. (NanoScience and Technology,, 2009)
Since the original publication of Noncontact Atomic Force Microscopy in 2002, the noncontact atomic force microscope (NC-AFM) has achieved remarkable progress. This second treatment deals with the following outstanding recent results obtained with atomic resolution since then: force spectroscopy and mapping with atomic resolution; tuning fork; atomic manipulation; magnetic exchange force microscopy; atomic and molecular imaging in liquids; and other new technologies. These results and technologies are now helping evolve NC-AFM toward practical tools for characterization and manipulation of individual atoms/molecules and nanostructures with atomic/subatomic resolution. Therefore, the book exemplifies how NC-AFM has become a crucial tool for the expanding fields of nanoscience and nanotechnology.